Pengaruh Strategi Diferensiasi dan Promosi terhadap Keunggulan Bersaing Maskapai Penerbangan Garuda Indonesia - Tarigan, Nerys Lourensius L.; Jayaningrum, Siti Kusandhitasari; Kinasih, Evityasakti Jaya (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Garuda Indonesia airline, the first and longest serving airline in Indonesia, cannot be separated from the Indonesian aviation industry. Garuda Indonesia is a pioneer in the Indonesian aviation business industry which faces tough competition from other airlines. Garuda Indonesia must have a plan to capture both new and existing markets in order to compete effectively. This study aims to determine and analyze the effect of differentiation and promotion strategies on the competitive advantage of Garuda Indonesia Airline. The data collection method used in this study was distributing questionnaires. The population used is Garuda Indonesia airline service users. The sample in this study were 80 respondents and the technique used was Non-Probability Sampling with a Purposive Sampling approach. This study uses multiple linear regression analysis as a method of data analysis. With the regression equation Y = 0.330 + 0.300 X1 + 0.613 X2. The results of this study indicate that the Differentiation Strategy has a significant effect on Competitive Advantage while Promotion has a significant effect on Competitive Advantage.